The Socialist Vision - (Bukluran sa Ikauunlad ng Sosyalistang Isip at Gawa), BISIG (Kasarinlan: Philippine Journal of Third World Studies, 2007)
The document is a preliminary attempt to conceptualize the principles and guidepost of a Philippine socialism that is not a mere copy of foreign models but one that is based on a critique of existing socialist states and a creative application of the socialist ideology to Philippine reality.